Rescuing the Zygote Argument - De Marco, G (Springer, 2015)
In a recent paper, Kristin Mickelson argues that Alfred Mele’s Zygote Argument, a popular argument for the claim that the truth of determinism would preclude free action or moral responsibility, is not valid. This sort of objection is meant to generalize to various manipulation arguments. According to Mickelson, the only way to make such arguments valid is to supplement them with an argument that is an inference to the best explanation. In this paper, I argue that there are two other ways in which the proponent of such manipulation arguments can modify their argument, neither of which requires an inference to the best explanation. I then briefly consider and respond to a worry with one of these proposed solutions.